Model development and process simulation of postcombustion carbon capture technology with aqueous AMP/PZ solvent. (April 2016) - van der Spek, Mijndert; Arendsen, Richard; Ramirez, Andrea; Faaij, André
Highlights: A process model was developed for the quaternary AMP–PZ–H2 O–CO2 system. The model was validated against experimental literature data. The model was used to simulate CO2 capture from an ASC Pulverised Coal power plant flue gas. The AMP/PZ solvent showed a significant technical improvement versus the incumbent MEA solvent. Pedigree analysis was used to assess the quality of the model. Abstract: This study presents the development, application, and uncertainty analysis of a process simulation model for postcombustion CO2 capture with an AMP/PZ solvent blend based on state of the art knowledge on AMP/PZ solvent technology. The development includes the improvement of the physical property models of a software package designed for simulation of acid gas treatment and CO2 capture technologies. The improvement particularly consisted of regression of AMP–PZ binary interaction parameters. The model was applied to a case study of postcombustion CO2 capture from an Advanced Super Critical Pulverized Coal power plant. Uncertainly analysis was undertaken by validating the physical property models against laboratory measurements reported in literature; by comparing model results with pilot study results, and by evaluating the strength of the model with a novel method called pedigree analysis. The results show that AMP/PZ postcombustion technology performs better than MEA technology on most performance indicators, e.g., the Specific Reboiler Duty is reduced from 3.6 GJ/t CO2 for MEA, to 2.9 GJ/t CO2 for AMP/PZ, and the specific cooling water requirement is reduced from 4.1 to 3.4 GJ/t CO2 . Only amine slip to the atmosphere increases with AMP/PZ technology: from 0.18 g/t CO2 to 15.3 g/t CO2, although this value is still within emission limits from existing regulatory frameworks. The coal power plant net efficiency with AMP/PZ capture amounts to a value of 37.2%LHV, compared to 46.1%LHV for the case without CCS and 36.2%LHV in case of CCS with MEA. The uncertainty analysis shows that the model is well capable of predicting experimental and pilot result. The remaining uncertainty is mostly in the reaction kinetics and in the flowsheet design. Validation could be further improved, by more elaborate comparison to independent measures of physical properties, and by comparison of the model outputs to results from large demonstration or commercial size capture plants.